Fusion of full-field optical angiography images via gradient feature detection - Wang, Gao; Li, Jiangwei; Tan, Haishu; Li, Xiaosong (Frontiers in Physics, 2024)
Full-field optical angiography (FFOA)-a real-time non-invasive imaging technique for extracting biological blood microcirculation informationcontributes to an in-depth understanding of the functional and pathological changes of biological tissues. However, owing to the limitation of the depth-offield (DOF) of optical lenses, existing FFOA imaging methods cannot capture an image containing every blood-flow information. To address this problem, this study develops a long-DOF full-field optical angiography imaging system and proposes a novel multi-focus image fusion scheme to expand the DOF. First, FFOA images with different focal lengths are acquired by the absorption intensity fluctuation modulation effect. Second, an image fusion scheme based on gradient feature detection in a nonsubsampled contourlet transform domain is developed to capture focus features from FFOA images and synthesize an all-focused image. Specifically, FFOA images are decomposed by NSCT into coefficients and lowfrequency difference images; thereafter, two gradient feature detection-based fusion rules are used to select the pre-fused coefficients. The experimental results of both phantom and animal cases show that the proposed fusion method can effectively extend the DOF and address practical FFOA image defocusing problems. The fused FFOA image can provide a more comprehensive description of blood information than a single FFOA image.